A Study of Using Authentic Supplementary Tasks In Teaching Speaking To 10 Grade Students At Doan Thuong Upper-Secondary School, Hai Duong Province = Nghiên Cứu Việc Sử Dụng Nhiệm Vụ Bổ Trợ Xác Thực Để Dạy Kỹ Năng Nói Cho Học Sinh Lớp 10 Trường THPT Đoàn T - Vũ, Thị Quyên (University of Languages and International Studies, 2017)
M.A. Thesis English teaching methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2012